Dominant inheritance in a family with primary atrophic rhinitis. - Sibert, J R (1980)
Primary atrophic rhinitis is an uncommon condition which presents with crusts in the nose. The nasal mucosa is dry and atrophied and the nasal cavities are abnormally wide. We report a large London Irish family with an affected father with fifteen children. Eight of these have primary atrophic rhinitis. Symptoms appear around puberty, and there was one case in the third generation with an affected mother. The nasal appearances of the affected members varied considerably and many hid their disease well. The family fits well with dominant inheritance. A familial aetiology for primary atrophic rhinitis is a more attractive theory than those previously postulated.